1997
DOI: 10.1016/s0014-5793(97)00579-6
|View full text |Cite
|
Sign up to set email alerts
|

Activation of translation initiation factor eIF2B by insulin requires phosphatidyl inositol 3‐kinase

Abstract: Eukaryotic initiation factor eIF2B mediates a key regulatory step in peptide-chain initiation and is acutely activated by insulin, although it is not clear how. Inhibitors of phosphatidylinositide 3-kinase blocked activation of eIF2B, although rapamycin, which inhibits the p70 S6 kinase pathway, did not. Furthermore, a dominant negative mutant of PI 3-kinase also prevented activation of eIF2B, while a Sos-mutant, which blocks MAP kinase activation, did not. The data demonstrate that a pathway distinct from MAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 42 publications
6
76
2
Order By: Relevance
“…We performed a full analysis of limiting factors eIF4F and eIF2. eIF2-mediated ternary complex formation is negatively regulated by phosphorylation of eIF2␣ subunit activated by several stimuli (18,(20)(21)(22)(23)(24)(25). Deprivation of matrix attachment strongly induced phosphorylation of eIF2␣, but left eIF4F formation almost unchanged (Fig.…”
Section: Pi3k Activation Does Not Restore Translation In Attachment-dmentioning
confidence: 93%
See 1 more Smart Citation
“…We performed a full analysis of limiting factors eIF4F and eIF2. eIF2-mediated ternary complex formation is negatively regulated by phosphorylation of eIF2␣ subunit activated by several stimuli (18,(20)(21)(22)(23)(24)(25). Deprivation of matrix attachment strongly induced phosphorylation of eIF2␣, but left eIF4F formation almost unchanged (Fig.…”
Section: Pi3k Activation Does Not Restore Translation In Attachment-dmentioning
confidence: 93%
“…In mammals, eIF2-␣ mediated down-regulation of translation is under the control of four different eIF2-␣ kinases and occurs in response to negative conditions for growth as diverse as amino acid deprivation (17), iron deficiency (18), heat shock and viral infection (19), endoplasmic reticulum stress (20,21), and UV exposure (22,23). Additionally, eIF2B activity is modulated by a PI3K-glycogen synthase kinase-3 pathway (24,25). Thus, the combination of different pathways converging to the translational machinery results in quantitative and qualitative changes of the mRNAs to be translated.…”
mentioning
confidence: 99%
“…Thus another PI 3-kinase-linked signalling pathway must be responsible for this, and this would be entirely consistent with the operation of the pathway depicted in Scheme 4. Welsh et al [84] have recently shown that PI 3-kinase is required for the activation of eIF2B, using both specific inhibitors of this enzyme and dominant negative mutants of the p85 subunit of PI 3-kinase. In contrast, neither MAP kinase nor the FRAP pathway seem to be required for the activation of eIF2B.…”
Section: Scheme 4 Signalling Pathway Likely To Be Involved In the Regmentioning
confidence: 99%
“…IGF-1 regulates the Akt/mTOR and the Akt/GSK-3␤ signaling pathways, which are involved in the skeletal muscle hypertrophy process by activating downstream regulators of protein initiation and translation. 19 In the elderly when compared to younger subjects, a reduction on the total protein content of several protein initiation and translation targets, such as mTOR, p70s6k, 4E-BP1, and eIF2B, all of which are either direct or indirect targets of Akt, [20][21][22] have been observed. 23 Additionally, the sensitivity and responsiveness of these proteins to stimulation via administration of essential amino acids are reduced in older subjects.…”
Section: Introduction Smentioning
confidence: 99%